Life and Death Sometimes Coincide, and Pastoral Response is Crucial to the Brokenhearted - Sergi, Consolato M. (Journal of pastoral care & counseling, 2022)
Perinatal loss may remain unexplained, despite current technology, modern preventive care measures, and advanced diagnostic procedures. Culturally sensitive and competent discussions should be prioritized in medicine, but religious and spiritual feelings are often marginalized. Here we highlight our reflections on the importance of the spiritual and theological responses to parents grieving stillbirth. Chaplains are critical for the wellbeing of both families and physicians.